Pan-London Network for Psychosis-Prevention (PNP) - Fusar-Poli, Paolo; Estradé, Andrés; Spencer, Tom J.; Gupta, Susham; Murguia-Asensio, Silvia; Eranti, Savithasri; Wilding, Kerry; Andlauer, Olivier; Buhagiar, Jonathan; Smith, Martin; Fitzell, Sharon; Sear, Victoria; et al. (Frontiers in Psychiatry, 2019)
Background The empirical success of the Clinical High Risk for Psychosis (CHR-P) paradigm is determined by the concurrent integration of efficient detection of cases at-risk, accurate prognosis and effective preventive treatment within specialised clinical services. The characteristics of the CHR-P services are relatively under-investigated. Method A Pan-London Network for Psychosis-prevention (PNP) was created across urban CHR-P services. These services were surveyed to collect: description of the service and catchment area, outreach, service users, interventions and outcomes. The results were analysed with descriptive statistics and Kaplan Meier failure function. Results The PNP included five CHR-P services across two NHS Trusts: Outreach and Support In South-London (OASIS) in Lambeth and Southwark, OASIS in Croydon and Lewisham, Tower Hamlets Early Detection Service (THEDS), City & Hackney At-Risk Mental State Service (HEADS UP) and Newham Early Intervention Service (NEIS). The PNP serves a total population of 2,318,515 Londoners (830,889 aged 16-35), with a yearly recruitment capacity of 220 CHR-P individuals (age 22.55). Standalone teams (OASIS and THEDS) are more established and successful than teams that share their resources with other mental health services (HEADS UP, NEIS). Characteristics of the catchment areas, outreach and service users, differ across PNP services; all of them offer psychotherapy to prevent psychosis. The PNP is supporting several CHR-P translational research projects. Conclusions The PNP is the largest CHR-P clinical network in the UK; it represents a reference benchmark for implementing detection, prognosis and care in the real-world clinical routine as well as for translating research innovations into practice.